2010
DOI: 10.3892/ijmm_00000457
|View full text |Cite
|
Sign up to set email alerts
|

Identification of lipid droplet-associated proteins in the formation of macrophage-derived foam cells using microarrays

Abstract: Abstract.A large number of macrophage-derived foam cells stores excessive neutral lipids in intracellular droplets, and plays a major role during the development of atherosclerosis. The formation and catabolism of intracellular lipid droplets (LDs) are regulated by LD-associated proteins, a group of proteins which are located on the surface of LDs and regulate the formation, morphology and lipolysis of LDs. In order to illustrate the function of LD-associated proteins during the process of atherosclerosis, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…PPAR-γ promotes the differentiation of macrophages into fatty macrophages in atherosclerotic plaques, and once differentiated, these cells highly express ApoE, FSP27 and ACAT1. 52,53 In the current study, elevations in PPAR-γ and ApoE were observed in torn rotator cuff muscles, although no changes in ACAT1 or FSP27 were present. Additionally, we observed fatty macrophages that accumulate around lipid plaques in T-cell deficient rats via immunohistochemistry.…”
Section: Discussionsupporting
confidence: 39%
“…PPAR-γ promotes the differentiation of macrophages into fatty macrophages in atherosclerotic plaques, and once differentiated, these cells highly express ApoE, FSP27 and ACAT1. 52,53 In the current study, elevations in PPAR-γ and ApoE were observed in torn rotator cuff muscles, although no changes in ACAT1 or FSP27 were present. Additionally, we observed fatty macrophages that accumulate around lipid plaques in T-cell deficient rats via immunohistochemistry.…”
Section: Discussionsupporting
confidence: 39%
“…In atherosclerosis, a population of fatty macrophages, often referred to as “foam cells”, uptake high levels of lipid and promote local tissue inflammation 7 . Activation of the transcription factor PPAR-γ plays an important role in the differentiation of fatty macrophages, which upon differentiation express high levels of Apolipoprotein E (ApoE) and FSP27 at high levels 24; 48 . In the current study, substantial elevations in PPAR-γ, ApoE and FSP27 were observed.…”
Section: Discussionmentioning
confidence: 99%
“…In fatty atherosclerotic plaques, macrophages differentiate into a “foam cell” phenotype and serve as the core cellular component of the plaque (47). Once they have differentiated into foam cells, they express Apolipoprotein E (ApoE) and CIDEC at high levels (58). ApoE is a central component of very-low density lipoproteins and chylomicron particles (58), and CIDEC plays an important role in lipid droplet formation and fat metabolism (59).…”
Section: Discussionmentioning
confidence: 99%